2011
DOI: 10.1002/lary.21750
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a TORS program in an academic medical center

Abstract: The introduction of a TORS program in an academic medical center can be a complex and daunting undertaking. We demonstrate that with careful planning, excellent efficiency and safety can be attained immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In contrast to non-TORS surgical approaches in which pharyngotomy and mandibulotomy are frequently required for access, multiple institutional series have demonstrated TORS to have short hospital length of stays (LOS) and decreased morbidity and mortality. [17][18][19][20][21] Our analysis of nationwide inpatient data demonstrates that TORS is associated with a decreased length of hospital stay and hospitalrelated costs, and also is associated with a lower rate of gastrostomy tube and tracheotomy tube placement compared to other surgical techniques. Furthermore, we found that TORS is not associated with acute morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to non-TORS surgical approaches in which pharyngotomy and mandibulotomy are frequently required for access, multiple institutional series have demonstrated TORS to have short hospital length of stays (LOS) and decreased morbidity and mortality. [17][18][19][20][21] Our analysis of nationwide inpatient data demonstrates that TORS is associated with a decreased length of hospital stay and hospitalrelated costs, and also is associated with a lower rate of gastrostomy tube and tracheotomy tube placement compared to other surgical techniques. Furthermore, we found that TORS is not associated with acute morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was no significant difference in operation time and console time between the earlier and later cases and correlation of console time with specimen size was significant. Another study reported that there were no significant differences in either of the two times between the initial and subsequent 10 cases or the first 15 and last 5 cases [ 20 ]. On the other hand, White et al [ 21 ] reported that the operating time decreased as experience with TORS increased.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report in the literature discussed the implementation of a TORS program in a tertiary academic medical center and outlined a suggested plan to rapidly achieve an acceptable "steady-state of efficiency." 8 One of the goals of this article was to highlight certain expected milestones that may reasonably be achieved after a set number of cases are performed. Programs that are in the beginning phase of their TORS experience commonly want to know how many cases it will take to achieve a reasonable operative time, among other end points.…”
Section: Discussionmentioning
confidence: 99%